Avaliação do benefício da intervenção fonoaudiológica em adultos e idosos com tontura - Rosa, Luiza Diniz da (2016)
INTRODUCTION: Dizziness is a very common symptom and it affects mainly adults and the elderly. It can lead to significant damage, disrupting the patient´s quality of life. Considering the high prevalence of reported dizziness in the population, many studies have been carried out in order to both identify its possible causes and develop speech therapy intervention techniques. OBJECTIVE: To evaluate the benefits of speech therapy intervention in adults and elderly people with dizziness. METHOD: Prospective and longitudinal clinical study conducted on a sample of 20 patients with complaints of dizziness, of both sexes and aged between 48 and 85 years of age (average of 66 years of age). All subjects were referred to vestibular rehabilitation by medical indication and they underwent ten sessions of exercises based and adapted from the Cawthorne (1944) and Cooksey (1946) Protocol. In addition, we applied the Dizziness Handicap Inventory (DHI), the Geriatric Depression Scale (GDS) and the Dizziness Quantification Scale questionnaires in three moments: before the intervention, at the fifth session of speech therapy intervention and after the tenth session. At the end of the ten sessions, all subjects answered a question concerning the improvement of the dizziness symptomatology. We used the questionnaires in the three moments of intervention both for comparison purposes and for the assessment of the effectiveness of the treatment. RESULTS: After the intervention, 17 subjects (85%) showed improvement in the DHI score and 18 (90%) reported improvement in the dizziness symptomatology. In spite of the fact that the three tests had a decrease in average in the three moments, we observed intervention interference only in relation to the DHI. The symptoms of depression, anxiety and insecurity were considered as influence variables in the intervention results. Cronbach’s Alpha showed that the DHI delivers a good consistency level, whereas GDS-5 showed only reasonable significance. CONCLUSION: The speech therapy intervention on dizziness proved to be effective. We observed there was a greater benefit in the 10-session intervention, when compared to the 5-session intervention. The use of questionnaires to assess the result of the interventions is an important instrument in the assessment of the treatment effectiveness. However, self-reference and clinical hearing should be taken into account